Country-of-origin labelling in the globalizing agrifood industry – the example of pork ‘made in Germany’ - Klein, Oliver (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
The provenance of food has without any doubt become more important in recent years which is not least reflected in the commercial launch of relevant labels. Especially in the era of an increasingly globalizing agrifood sector, the emphasis on country-of-origin effects could appear as an additional selling point. This is also true for the pork industry which will be shown by using the example of pork ‘made in Germany’. Therefore, the current export success of German pork is obviously a result of positive quality features which are (subjectively) derived from the national provenance. The growing demand for ‘quality pork made in Germany’ in several East Asian markets, which are particularly important due to remarkable value-added potentials, has led pork producers to highlight the ‘benefits’ of German origin and to accordingly shape their upstream supply relations. As a result of this, pig fattening farmers who import their pigs from Denmark or the Netherlands are excluded from these production lines. The emphasis on country-of-origin effects is thus accompanied by modifications of the spatial organization of production networks.